MAKNA KONSELING DALAM KITAB SUCI - Steven Tubagus (Institut Agama Kristen Negeri Manado, 2020)
ABSTRACT The counseling crisis is felt by everyone, lacking trust in the counselor. Based on that, it is necessary to contribute to pastoral counseling in guiding according to the scriptures. The Meaning of Counseling in the Scriptures. The purpose of this paper is to describe the meaning of counseling in the scriptures theologically. The method used is qualitative, using literature studies, namely the Bible and reference books. The results of the study are pastoral counseling that God loves all people regardless of our lives filled with sin though. The meaning of Counseling in the Scriptures is first, to become a new creation in Christ. Second, Have a New Mind for the New World. Third, Have a New Heart. Fourth, become a disciple of Jesus